Tablet effervescent dari ekstrak daun alpukat (persea americana mill.) sebagai peluruh batu ginjal pada tikus jantan galur wistar (ratus norvegicus) - Damayanti, Novi Amna; I Gusti Ngurah Agung Dewantara Putra; Eka Indra Setyawan (Program Studi Akuntansi IKOPIN, 2022)
Chemical compounds found in the avocado leaf, include saponins, tannins, phlobatannins, flavonoids, alkaloids, and polysaccharides. Avocado leaf can be used as medicinal herbs for kidney stones and hypertension. Avocado leaf extract can reduce the formation of calcium oxalate monohydrate crystals, which is the main component of kidney stones and shows changes in morphology and crystal size. Other studies showed that avocado leaf extract effervescent tablets have a kidney stone laxative effect. Effervescent tablets were made from the ethanol extract of the avocado leaf with 3 variations in levels in each formula. The variations in the avocado leaf extract level used in formulas 1, 2, and 3 were 35, 65, and 100 mg in a row. The results showed that formula 3 with avocado leaf extract of 100 mg gave the most significant results as a kidney stone laxative when compared to other formulas.